Catalase-like quantum dots of l-lysine polymerization as free radical scavengers for hypoxic brain injury. (June 2021) - Li, Qifeng; Gao, Yalong; Shen, Jun; Mu, Xiaoyu; Wang, Junying; Ouyang, Lufei; Chen, Ke; He, Hua; Pei, Jiahui; Ren, Qinjuan; Sun, Si; Liu, Haile; et al.
Graphical abstract: Abstract: Hypoxemia as one of the most common symptoms of traumatic brain injury (TBI) can significantly exacerbate the development of secondary damage, which further contributes to generating large numbers of neurotoxic factors such as reactive oxygen and nitrogen species (RONS), pro-inflammatory cytokine and chemokine. Here, we developed a kind of quantum dots as catalase-mimic and multiple free radical scavengers by means of the microwave heating polymerization of l -lysine. Hydrogen peroxide as overproduced radicals can be decomposed to supply oxygen, contributing to improving the hypoxic condition in brain. Simultaneously, other traditional RONS such as O2 −, OH, NO and ONOO − can be eliminated by the quantum dots. The total ROS level is back to normal after the quantum dots treatment, promoting the H2 O2 /LPS-stimulated cell survival in vitro . Oxidative stress induced by hypoxic brain injury is restored by the quantum dots intravenous injection, leading to the protection of neural cells in vivo . Additionally, the quantum dots can improve the spatial learning and memory of TBI mice by water maze test. This work provides a new perspective for the therapy of hypoxic brain injury.